(3GdCSGdjH GdcejI aj GdJShjb (B/s - (3GdUejOYj, eMehOs; (3QOjfI, YKeGf jhSas ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2006)
(3eONd JegjOj aj JWhQ eaghe GdJShjb, GdShb, GSJNOGe HYV GdCSGdjH GdcejI aj OQGSI GdefJL, GdCSGdjH GdcejI aj GdJSYjQ, GdCSGdjH GdcejI aj GdJhRjY, GdCSGdjH GdcejI aj GdJQhjL, WQb GdJfHD HGdeHjYGJ, GdGJLGgGJ GdcejI aj OQGSI Sdhc GdeSJgdc, GdHQeLI GdNWjI(B.s
(3eQGLY U(B.311s
Keywords: (3GdJShjbs; (3GdJShjb(B- (3GdWQb GdGMUGFjI s